Effect of Light-emitting Diodes, Ultraviolet-B, and Fluorescent Supplemental Greenhouse Lights on Strawberry Plant Growth and Response to Infection by the Anthracnose Pathogen Colletotrichum gloeosporioides - Barbara J. Smith; Amir Rezazadeh; Eric T. Stafne; Hamidou F. Sakhanokho (HortScience, 2022)
Supplemental lighting is frequently used to extend daylength for strawberries (Fragaria ×ananassa) grown in greenhouses and high tunnels; however, information is limited on the effect of these lights on disease development. We evaluated the effect of ambient light and six supplemental light treatments [red, blue, and white light-emitting diodes (LEDs), separately; a combination of red, blue, and white LEDs; wide-spectrum fluorescent (WSF); and WFS + ultraviolet B (UV-B)] on plant growth and disease response of strawberries grown in a greenhouse. Plants were exposed to supplemental light treatments for 17 h each day. In the WSF+UV-B treatment, plants were exposed to WSF light during the day and to UV-B light for 3 hours during the night. Two trials were conducted; each trial contained five or six cultivars and was replicated three times. Twice during each trial, detached leaves from each cultivar in each light treatment were inoculated with a conidial suspension of the anthracnose crown rot pathogen, Colletotrichum gloeosporioides and rated for disease severity 10 days later. There was a significant difference due to light treatment and to cultivar in relative chlorophyll content and plant growth parameters. Plant injury ratings were lowest in the white LED, WSF, and WSF+UV-B treatments. Plants in the combination LED and red LED light treatments received higher injury, lower vigor scores, and lower relative chlorophyll content values than plants in all other light treatments. After inoculation of detached strawberry leaves with C. gloeosporioides in Trial 1, there was a significant effect due to light treatments on disease severity ratings (DSRs) after 18 weeks’ exposure to light treatments with the DSRs in the WSF+UV-B treatment being lower than those in all other treatments except those in the red LED treatment. There was not a significant effect in DSRs due to light treatments after 24 weeks in Trial 1 or after 4 or 22 weeks in Trial 2. There were significant effects due to cultivar on DSRs in both trials: ‘Strawberry Festival’, ‘Pelican’, and ‘Seascape’ received the lowest DSRs. This study showed an effect of supplemental light on several strawberry plant growth parameters, including a harmful effect of high-intensity red LED irradiation.